Private conscience public morality - "Inglis, Brain" (London, 1964)
This book is not concerned to original thesis as to prevent a survey of ideas that have already been propounded and are beginning to establish themselves,it is not easy to do justice to the people most responsible for them.
Keywords: Ethics